Model for the Teaching of Occupational Health and Safety and Risk Management within the Science Curriculum. - Anonymous ([Committee for University Teaching and Staff Development], 1999)
This is a report from the Adelaide University on a project funded by the Committee for University Teaching and Staff Development. The report outlines in detail the completion of the project's objectives and provides in-depth discussion on the individual project modules: Honours Chemistry, Organic Chemistry 11 and Level 1 Chemistry.